Estimativas das necessidades de nitrogênio e aminoácidos sulfurados para gatos em crescimento - Sato, Joyce (2017)
Although there are many commercial cat foods, little is known about the protein and amino acid requirements for this species, which is considered strictly carnivorous with a high protein requirement. The Göttingen method is considered easy to perform, using only nitrogen balance variables. Through it is possible to estimate the need for nitrogen and limiting amino acid maintenance in the diet. With this in mind, this study aimed to at a first estimate the needs of nitrogen and sulfur amino acids (methionine and cystine) at Göttingen method , and then associate with health parameters as indicators of oxidative status, coat quality, and growth indicators for growing cats from 150-240 days of age. Thirty-six cats were employed in the study and the experimental period was 90 days (150-240 days of age). The animals were distributed in six treatments, according to weight and brood, each treatment consisting of six replicates. Nitrogen estimates for maintenance were 591, 517 and 457 mg / PV kg0.67 / d, according to each age 150, 195 and 240 days respectively. For methionine + cystine, a need was estimated for 581; 510 and 318 mg / PV kg0.67 / day for the animals in the same period. In the second moment, we sought to relate health parameters and nutrient intake (crude protein and methionine + cystine) and metabolizable energy, in which multivariate statistical methods were applied. The animals were divided into clusters of low, moderate and high protein, energetic and methionine + cystine intakes. The health parameters related to sulfur amino acids and protein were: hair resistance, hair growth, determination of the sulfur and hair amide bridges by Raman spectroscopy and FTIR (hair quality indicators); determination of reduced, oxidized glutathione and the relationship between both, Body composition and Biochemical parameters. An exploratory factorial analysis was performed to define factors that were: growth indicators, health indicators, indicators of nitrogen intake and indicators of hair resistance. The growth indicators were significant (P <0.05) in the comparison between low and moderate ingestion clusters, with the lowest results being obtained in the low cluster and the highest in the cluster of moderate ingestion. The nitrogen intake indicators had a significant effect (P <0.05) on the comparison between the low, moderate and high ingestion clusters, being a direct reflection of the increasing CP intake of the clusters. Diets containing CP levels above 85 g / 1000 kcal MS, E:P ratio below 12.4 kcal / g and M + C contents above 2.8 g / 1000 kcal appear to favor the health conditions of cats of 150-240 days of age. Energy intake below 153.22 kcal / PV kg0.67 / d appears to impair the performance of cats at this stage of growth.